Proses Pemaknaan Hidup dalam Novel Akik dan Penghimpun Senja Karya Afifah Afra dengan Pendekatan Logoterapi - Wahyuni, Tri (ALAYASASTRA, 2017)
This study reveals the life giving meaning process in Afifah Afra?s novel Akik dan Penghimpun Senja. The human giving meaning of life process was relatives depended on individual?s comprehension and competence read the signs on the universe. The aim of this study was describing the giving meaning of life of the characters in the novel, so the readers could get the guidances to face the phenomena occurs in the society by using Viktor Emil Frankl view of logotherapy. Afifah Afra?s novel Akik dan Penghimpun Senja delivers four points of giving meaning of life process such as (1) contemplation of creating humans and universe, (2) natural conservations and maintenance, (3) klenik and the cooperation between human and ghost phenomenon, and (4) human?s religion aspects. Keywords: giving meaning of life, literature, novel, logotherapy.